82 Does the CHA2S2VASC or R2-CHA2DS2VASC Predict Procedural and Short-term Outcomes in Patients Undergoing Transcatheter Aortic Valve Implantation. (31st May 2014) - Hamid, Tahir; Choudhury, Tawfiq; Anderson, Simon; Hashmi, Izhar; Roberts, David; Levy, Richard
Abstract : Introduction: Transcatheter aortic valve implantation (TAVI) is associated with peri and post-procedural morbidity and mortality. Currently there is a lack of an established scoring system to further stratify patients who are potential TAVI candidates. We used the CHA2 DS2 -Vasc score and a modified R2 CHADS-VASC score that we devised, (R2- for pre-existing Renal impairment, and pre-existing Rhythm abnormality (RBBB/LBBB) on ECG to determine if they predict mortality and morbidity in patients undergoing TAVI. Methods: The data source is a retrospective analysis of prospective data registry of consecutive patients who underwent TAVI at two tertiary centres between April 2008 and April 2013. Results: A total of 236 patients with severe aortic stenosis underwent TAVI. 215 patients received the CoreValve(®) (Medtronic Inc., Minneapolis, USA) prosthesis while 21 had Edwards-SAPIEN (Edward Lifesciences, Irvine, California) prosthesis.Mean age was 80 ± 8 years. Patients demographics included: 44% (103) female, 25% (59) diabetic, 67%(157) hypertensive, 44% (66), 60% (136) smokers and 27% (42) had chronic renal failure. 18 (12%) had previous transient ischaemic attacks or cerebrovascular accident. The 28-day mortality was 19.2% in those patients with a CHA2 DS2 -Vasc score of ≥6 whereas only 5.6% in those with a score <6 (p < 0.05). Using the R2 -CHA2 DS2 -Vasc score, the difference was more pronounced with a 28-day mortality of 25% in those patients with a R2 - CHA2 DS2 -Vasc score of ≥7 compared to 5.8% in those with a R2 - CHA2 DS2 -Vasc of <7 (p < 0.05). The 1yr mortality rates, however, were not statistically significantly associated with the CHA2 DS2 -Vasc or R2 - CHA2 DS2 -Vasc scores. Conclusion: Our study demonstrates the potential use of the CHA2 DS2 -Vasc Score and the modified R2-CHA2 DS2 -Vasc scores to risk stratify patients undergoing the TAVI procedure.